Klasifikasi ijtihad dan mujtahid dab kedudukan ijtihad dan fatwa dalam islam - Wulandari, Windi Kartika (Maliki Interdisciplinary Journal, 2025)
This paper discusses in detail the concept of ijtihad, the types of mujtahids, and the role of ijtihad and fatwa in the Islamic legal system. Ijtihad is defined as a mujtahid’s maximum effort to research and determine sharia law from primary sources such as the Qur’an and hadith, as well as additional sources such as ijma’ and qiyas. In practice, ijtihad has various classifications, both based on method, perpetrator, and legal object, which demonstrates the ability of Islamic law to adapt to various problems faced by the community. This paper also explains the various types of mujtahids, depending on the level of ability and the method of ijtihad used, ranging from absolute mujtahids to murajjih mujtahids. In addition, the relationship between ijtihad and fatwa is discussed, where the fatwa is the end result of the ijtihad process, although it is not always binding. Fatwa is a response to real problems, while ijtihad encompasses a broader legal analysis. In conclusion, ijtihad and fatwa are two crucial tools in the dynamics of Islamic law, which can only be implemented by individuals with adequate knowledge. Both play a crucial role in facing the challenges of the times while remaining grounded in sharia principles. Therefore, the existence of mujtahids and the strengthening of ijtihad institutions are crucial to maintaining the relevance and sustainability of Islamic law.